Photoshop elements 10 : for Windows and MAC OS X - Carlson, Jeff (Visual quickstart guide., 2012)
Perfect your photos and images with this "focused" guide to the latest version of Photoshop Elements. For most of us, the professional-level Photoshop is overkill for our needs. Amateur photographers and photo enthusiasts turn to Photoshop Elements for a powerful but simpler way to edit and retouch their snapshots --